Production of Mass-Separated Erbium-169 Towards the First Preclinical in vitro Investigations - Talip, Zeynep; Borgna, Francesca; Müller, Cristina; Ulrich, Jiri; Duchemin, Charlotte; Ramos, Joao P.; Stora, Thierry; Köster, Ulli; Nedjadi, Youcef; Gadelshin, Vadim; Fedosseev, Valentin N.; Juget, Frederic; et al. (Frontiers in Medicine, 2021)
The β--particle-emitting erbium-169 is a potential radionuclide towards therapy of metastasized cancer diseases. It can be produced in nuclear research reactors, irradiating isotopically-enriched 168Er2O3. This path, however, is not suitable for receptor-targeted radionuclide therapy, where high specific molar activities are required. In this study, an electromagnetic isotope separation technique was applied after neutron irradiation to boost the specific activity by separating 169Er from 168Er targets. The separation efficiency increased up to 0.5% using resonant laser ionization. A subsequent chemical purification process was developed as well as activity standardization of the radionuclidically pure 169Er. The quality of the 169Er product permitted radiolabeling and preclinical studies. A preliminary in vitro experiment was accomplished, using a 169Er-PSMA617, to show the potential of 169Er to reduce tumor cell viability.